Reconciling self-urban development practice and social justice - Jabeen, Huraera (BRAC University, 2010)
We live in a world that is full of contradictions, of multiple positionalties, and of highly contested meanings and aspirations. Trying to position oneself in this complex world requires an understanding of the power, constraints, possibilities and strategies to perform. From the 1990’s the movement of socioeconomics has challenged the established theoretical process of development practice. In planning practice changed role of planners has delegated him or her the responsibility to act as advocates for particular communities; as technical research staff who study issues long before they appear on decision-making agendas or as skilful mediator. The discourse of urban development practice in Bangladesh especially about reducing poverty is dominated by professionals- the staff of NGOs, government departments and international agencies rather than the affected people. In this essay I tried to define ‘me’ in the practice that gives me the opportunity and challenge to look at the trend of development practice and myself in different domains. To define my position I wanted to look at myself from three perspectives: in the domains of national, professional and social world. With them I wanted to determine some ‘code of practice’ that can be of any person’s interested to be a professional working in the urban development sector in Bangladesh to get the best possible option to become a linkage to establish social justice.